Study Abroad and Cultural Learning Through Fulbright and Other International Scholarships: A Holistic Student Development - Akli, Madalina (Journal of International Students, 2013)
This article focuses on one piece from the complex puzzle of internationalization, namely the intercultural learning during education abroad. It departs from a critical reflection on American student applications for the Fulbright program and uses the application process for Fulbright scholarship as a lynchpin for other study abroad scholarships for American students. It shows how the stages of before, during and after education abroad can be comprehensively integrated into a holistic process of student development in American universities. This process has the ultimate goal of helping American students function in an international context and redefining their world view to encompass the notion that cultures can be understood relative to one another.